Psychosocial Support Services in Efforts to Address Feelings of Weariness Among Residents of MedanPlus Rehabilitation Foundation - Yohanna Arminta Zega; Husni Thamrin (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research aims to tackle the challenge of boredom and weariness among residents in rehabilitation due to monotonous routines. It emphasizes the importance of psychosocial support to enhance engagement and emotional well-being during rehabilitation. Method: Employing a Social Group Work framework, the study involves stages like Preparation, Assessment, Program Planning, Implementation, and Evaluation. Qualitative data from residents' responses is analyzed to gauge the intervention's effectiveness. Practical Applications: This research informs rehabilitation practices by advocating positive activities and motivation to improve residents' experiences and emotional states. Tailored interventions can alleviate boredom and facilitate successful reintegration. Conclusion: This study improves rehabilitation outcomes by addressing boredom through psychosocial support. The Social Group Work approach effectively counters boredom and promotes positive emotions, enriching rehabilitation programs.